2022
DOI: 10.3390/s22051762
|View full text |Cite
|
Sign up to set email alerts
|

EEG Evoked Potentials to Repetitive Transcranial Magnetic Stimulation in Normal Volunteers: Inhibitory TMS EEG Evoked Potentials

Abstract: The impact of repetitive magnetic stimulation (rTMS) on cortex varies with stimulation parameters, so it would be useful to develop a biomarker to rapidly judge effects on cortical activity, including regions other than motor cortex. This study evaluated rTMS-evoked EEG potentials (TEP) after 1 Hz of motor cortex stimulation. New features are controls for baseline amplitude and comparison to control groups of sham stimulation. We delivered 200 test pulses at 0.20 Hz before and after 1500 treatment pulses at 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 71 publications
1
10
1
Order By: Relevance
“…Supporting this idea, a larger study with 46 participants following the same protocol replicated the increase in the N100 component but reported opposite results for the P60 component, showing a decrease in amplitude ( Zhou et al, 2022 ). The authors argued that the divergent findings are likely due to the larger sample size and methodological differences in TMS settings between the two studies ( Zhou et al, 2022 ). Zhou et al (2022) used 200 pulses and a stimulation intensity of 110% of the resting motor threshold (RMT) to improve signal-to-noise ratio, while Casula et al (2014) used a stimulation intensity of 120% RMT and 50 pulses.…”
Section: Primary Motor Cortex (M1)mentioning
confidence: 94%
See 2 more Smart Citations
“…Supporting this idea, a larger study with 46 participants following the same protocol replicated the increase in the N100 component but reported opposite results for the P60 component, showing a decrease in amplitude ( Zhou et al, 2022 ). The authors argued that the divergent findings are likely due to the larger sample size and methodological differences in TMS settings between the two studies ( Zhou et al, 2022 ). Zhou et al (2022) used 200 pulses and a stimulation intensity of 110% of the resting motor threshold (RMT) to improve signal-to-noise ratio, while Casula et al (2014) used a stimulation intensity of 120% RMT and 50 pulses.…”
Section: Primary Motor Cortex (M1)mentioning
confidence: 94%
“…Over this brain region, it is important to consider that single-pulse TMS typically evokes four distinct components in the recorded EEG signal: two positive peak at a latency of 30 (P30) and 60 ms (P60), and two negative peak at 45 ms (N45) and 100 ms (N100). In the context of rTMS protocols, which can induce after-effects on cortical excitability, two influential studies have investigated how TEPs are modulated following low-frequency rTMS ( Casula et al, 2014 ; Zhou et al, 2022 ). In the first study, Casula et al (2014) delivered 1 Hz rTMS over the left M1 to 15 healthy volunteers (HV) and observed increased amplitudes of the P60 and N100 components in the TEPs.…”
Section: Primary Motor Cortex (M1)mentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of rTMS-evoked EEG potentials can assess inhibition at any neocortical location. 92 After an initial uncontrolled study demonstrated antiseizure effects of rTMS at 0.33 Hz (with stimulation applied using a round coil over the vertex), 93 several sham-stimulation-controlled studies failed to reproduce this effect (with stimulation applied over the vertex or over the area of the epileptic focus), until more recently rTMS at 0.5 Hz and 90% resting motor potential (using a figureof-eight shaped coil over the epileptic focus) was shown to be effective in a controlled trial. 94 rTMS has also been used acutely in status epilepticus in case reports and small case series, and appears to be effective (though often only transiently).…”
Section: Noninvasive Stimulation For Epilepsymentioning
confidence: 99%
“…e N e u r o A c c e p t e d M a n u s c r i p t capable to modulate certain TEP components and that these could potentially serve as markers for neuroplastic changes (Casula et al, 2014;Thut and Pascual-Leone, 2010;Voineskos et al, 2021;Zhou et al, 2022). The majority of rTMS studies in combination with EEG investigated TEPs before and after rTMS (offline effects) (Tremblay et al, 2019).…”
Section: Introductionmentioning
confidence: 99%